Political and legal norms & factors of return of forced migrants to their homeland - Malynovska, Olena (Migration & Law, 2024)
The article is devoted to the review of political and legal norms and principles developed by the international community and aimed at ensuring the most desirable of possible long-term solutions to the refugees, namely, voluntary, safe and sustainable return to the homeland. In it are considered factors of the return of forced migrants, including their individual characteristics (age, gender, family composition, education, individual experience), structural factors, that is, the security and socio-economic situation in the country of origin and the situation in which refugees are in the country of refuge, as well as political factors, that is, the politics of host and origin countries, international humanitarian organizations. An analysis of repatriation flows, the policies of individual countries and international organizations that had to solve the problems of returning refugees was carried out. A conclusion was made about the expediency of using this experience in the formation of the forecast of the return of Ukrainian war refugees to the Motherland and the development of political decisions that will contribute to this, which is of not only scientific, but also practical interest. This experience shows, in particular, that return programs should be integrated into the general strategy of reconstruction and development of the country after the end of the conflict, providing not only assistance in moving, but also substantial support for the reintegration of returnees in their homeland. It also follows that effective solutions to facilitate repatriation can be found only under the condition of close cooperation between the countries of origin and residence of refugees and with the assistance of international humanitarian organizations. Such programs must be institutionally and resource-secured, developed on the basis of verified statistical and scientific data, be regionally oriented, take into account the interests of both returnees and the local population that did not leave anywhere. It is important to realize that return is not a one-time act, but a long-term process. Migrants’ strategies may involve not only returning home or staying abroad, but also a combination of these options, characterized by concepts such as temporary, cyclical, delayed, incomplete return. In this regard, measures to encourage return should be addressed not only to returnees themselves, but also to refugees who are currently still abroad, provide the protection of their rights and interests, development of relations with them in the interest of their possible return home.
Keywords: Refugees; Forced migrants; Voluntary, safe and sustainable return; Factors of return; Migration law; Migration policy